IPTEKS PENYUSUNAN APBD PROVINSI SULAWESI UTARA - Triyono, Nofriyanto; Wangkar, Anneke (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
The budget is prepared based on programs and activities that have been planned for a period of one year. For this reason, the Government through the Regional Head made a KUA draft which contained: (1) Revenue Policy, (2) Shopping Policy, (3) Financing Policy. In determining the KUA-PPAS budget allocation, regional financial management uses the money follow program priority approach, which is only to make priority programs that want to be done so that the budget can run efficiently. The general policy of the 2018 North Sulawesi provincial government budget is prepared by taking into account the regional macroeconomic aspects. The government continues to boost economic growth through regional taxes and levies to build a better North Sulawesi.Keywords: revenue, expenditure, financing policy